Edukasi Smart Farming melalui Buku Panduan Pembuatan Sensor Kelembapan Tanah Berbasis IoT di Desa Silungkang Oso - Armida Silvia Asriel; Zhafran Aziz; Rafif Ryo Dzaky; Salsa Billa Qolyum Nada; Urwatil Wusqa; Aditya Rudios Putra (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Farmers in Silungkang Oso village still rely on manual irrigation and fertilization based on subjective estimates. This can lead to water waste, inaccurate fertilizer application, and decreased soil productivity. Limited knowledge of agricultural technology is a significant barrier to the adoption of data-driven innovations at the village level. Therefore, this activity aims to improve farmers' knowledge by developing and implementing a guide. The guide covers the basics of soil moisture, the purpose and benefits of an IoT-based moisture sensor, steps for building a device using a capacitive sensor and an Arduino microcontroller, an operating manual, and the importance of this technology for more efficient farming. This initiative was implemented through direct farmer outreach and accompanying guidance to ensure their understanding of the guide. Results indicate that the guide effectively improved farmers' understanding and skills in handling smart farming concepts. This approach has the potential to serve as a model for technology-based agricultural education and can be applied in other rural areas to promote more precise and efficient farming.